A virus similar to human hepatitis B virus associated with hepatitis and hepatoma in woodchucks. - Summers, J (1978)
Particles with properties similar to those associated with human hepatitis B were found in serum from woodchucks with chronic hepatitis and hepatocellular carcinoma. It is suggested that woodchuck hepatitis virus is a second member of a novel class of viruses represented by the human hepatitis B virus.